Development of a Creative ui-Based Entrepreneurial Website to Attract Generation Z - Wiby Aldi Putra; Annona Benedicta; Evelyn Thelia; Randy Reynaldi Silitonga; David Nehemia Sunoto (International Journal Labs, 2025)
Technological developments have made websites the primary medium for entrepreneurial activities, especially among Generation Z, the largest internet users today. However, among many entrepreneurial websites, not all have succeeded in attracting Generation Z's interest. Websites with monotonous and less attractive displays tend to be abandoned by users, so a creative and relevant User Interface design is needed for Generation Z. This study aims to analyze the influence of creative User Interface design on Generation Z's interest in using entrepreneurial websites, while also producing a website prototype according to the preferences collected. The research method used is Research and Development (R&D) with a 3D model (Define, Design, Develop) using a questionnaire to identify design elements that suit Generation Z's interests, accompanied by a literature study to strengthen the theory. The results of the study show that Generation Z has a higher interest in creative User Interface designs that comply with the guidelines. Developed prototype has also been designed based on expert validation results, so it is considered capable of attracting user interest. This study proves that the application of creative User Interface design influences Generation Z's interest in using an entrepreneurial website.